2020
DOI: 10.1111/irv.12825
|View full text |Cite
|
Sign up to set email alerts
|

What is the long‐term clinical significance of anti‐SARS‐CoV‐2‐specific IgG?

Abstract: We read with great interest the article "Clinical significance of SARS-CoV-2-specific IgG detection with a rapid antibody kit for COVID-19 patients" by Chong et al 1 The manuscript discusses the possible implications of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-specific Immunoglobulin G (IgG) production and the concomitant positivity in SARS-CoV-2 detection by polymerase chain reaction (PCR) in asymptomatic and symptomatic patients. This study raises some interesting questions, and we would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Importantly, reports have identified that asymptomatic, moderate, and severe COVID-19 present different IgM and IgG production courses and may vary in quantity. Severe COVID-19 patients produce anti-SARS-CoV-2 IgG earlier in comparison to moderate patients, and asymptomatic and mild patients produce less neutralizing antibodies in comparison to moderate and severe COVID-19 patients [52].…”
Section: Antibodies and B Cellsmentioning
confidence: 88%
See 2 more Smart Citations
“…Importantly, reports have identified that asymptomatic, moderate, and severe COVID-19 present different IgM and IgG production courses and may vary in quantity. Severe COVID-19 patients produce anti-SARS-CoV-2 IgG earlier in comparison to moderate patients, and asymptomatic and mild patients produce less neutralizing antibodies in comparison to moderate and severe COVID-19 patients [52].…”
Section: Antibodies and B Cellsmentioning
confidence: 88%
“…More importantly, serum antibody titers rapidly decay after COVID-19, with conflicting reports with antibody titers decaying after a few months post-diagnosis [53,54]. Nevertheless, antigen-specific memory B cells [55], T cells, and other components of the immunological memory remain effective and can be detected in convalescent patients [52,56]. As memory cells can rapidly respond upon subsequent antigen encounter (infection), some degree of long-term immunity is expected [57].…”
Section: Antibodies and B Cellsmentioning
confidence: 99%
See 1 more Smart Citation